2017
DOI: 10.24832/sba.v18i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Budaya Austronesia Di Indonesia Bagian Barat Dalam Kaitannya Dengan Migrasi Out Of Taiwan

Abstract: AbstrakOut Of Taiwan merupakan salah satu teori persebaran Austronesia yang paling populer diikuti oleh kalangan peneliti manusia pendukung dan budaya Austronesia hingga kini. Populernya teori tersebut tidak lepas dari dukungan data linguistik, antropologi, DNA, pertanggalan dan data arkeologis tentunya. Data arkeologis yang cukup besar memberikan andil dalam eksistensi teori dimaksud di antaranya adalah hipotesis sebaran beliung persegi dan kapak lonjong. Migrasi atas dasar tersebut menunjukkan adanya alur pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…The similarity of the red-slipped pottery of Loyang Mendale and Loyang Ujung Karang in terms of decorative patterns and dating with the pottery at the Ban Chiang site in Thailand further corroborates the migration of Austronesian speakers through the WRM route. Moreover, according to Wiradnyana, there are fragments of red-slipped pottery that are dated older than the Minanga Sipakko site, the oldest prehistoric Austronesian site in Indonesia (Wiradnyana, 2017).…”
Section: Review the Construction Of The Textual Understanding Of Gayomentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity of the red-slipped pottery of Loyang Mendale and Loyang Ujung Karang in terms of decorative patterns and dating with the pottery at the Ban Chiang site in Thailand further corroborates the migration of Austronesian speakers through the WRM route. Moreover, according to Wiradnyana, there are fragments of red-slipped pottery that are dated older than the Minanga Sipakko site, the oldest prehistoric Austronesian site in Indonesia (Wiradnyana, 2017).…”
Section: Review the Construction Of The Textual Understanding Of Gayomentioning
confidence: 99%
“…Thus it can be concluded that there has been an exploration of the area carried out by the Hoabinhian group in the coastal area. The exploration of the area is very likely based on the subsistence pattern of the Hoabinhian group as food gatherers and gatherers (Wiradnyana, 2017).…”
Section: Review the Construction Of The Textual Understanding Of Gayomentioning
confidence: 99%
“…Penyebaran ke wilayah barat kemungkinan mengikuti alur darat hingga ke Thailand kemudian mengikuti aliran Sungai Perak yang berhulu di wilayah Thailand mengalir sampai di wilayah Kerajaan Perak Malaysia, dan akhirnya sampai di kawasan Sumatera bagian utara. Alur lain yang dimungkinkan adalah melalui jalur China bagian selatan terus ke Taiwan kemudian ke Filipina untuk kemudian ke Kalimantan dan terus ke Sumatera bagian utara (Wiradnyana, 2017). Migrasi para penutur Austronesia tidak berhenti di Sumatera bagian utara tetapi terus menyebar ke selatan.…”
Section: Bukti-bukti Pewarisan Budayaunclassified
“…Selanjutnya, wilayah Nusantara didatangi oleh bangsa Austronesia yang terjadi dalam dua gelombang migrasi (Wiradnyana, 2015). Proto melayu (melayu tua) merupakan sebutan untuk gelombang migrasi pertama yang terjadi sekitar 3000-1500 SM.…”
Section: Pendahuluanunclassified